Contagion effect of COVID-19 on stock market returns: Role of gold prices, real estate prices, and US dollar exchange rate - Naveed Iqbal Chaudhry; Humaira Asad; Mahwish Abdulghaffar; Muhammad Amir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
The purpose of this study is to empirically analyze the contagion effects of the COVID-19 pandemic on stock returns of the Pakistan Stock Exchange (PSX). In this context, the causal changes of three major macroeconomic indicators i.e. gold prices, prices of real estate, and the US exchange rate on the stock market returns were assessed. The daily indices of stock returns, house prices index, plot price index, daily prices of gold, and the daily US dollar exchange rate are analyzed. The data spanning six months, including three months of pre-COVID-19 and three months of post-COVID-19, was analyzed using E-viewssoftware. The event study methodology is used, and the GARCH model is applied totest the relations. The findings highlight the impact of the COVID-19pandemic on stock returns and reveal a significant change in the relationship between prices of gold and the stock market returns. Similarly, the change in the relationsbetween stock market returns and real estate prices got significant support. However,the change in the relationsbetween the US dollar exchange rate and stock market returns was found insignificant. Thestudy contributes by providing evidence that explains the changes in dynamics of the capital market during the pandemic. The study alsohelpsthe investors to understand how macroeconomic variables behave during periods of stress.
Keywords: 330; COVID-19; Pakistan Stock Exchange (PSX); contagion effect; gold prices; real estate prices; US dollar exchange rate